The role of artificial intelligence and emerging technologies in UAE commercial transactions law (2023) - Allouzi, Adel Salem; KRIM, Karima; AlKhamaiseh, Mohammad Abdalhafid (Research Journal in Advanced Humanities, 2024)
In light of the Fourth Industrial Revolution, the intervention of artificial intelligence in commercial transactions has expanded significantly. It has not remained merely a subject or object of the contract, whether as a material or moral product. However, it has progressed to play a fundamental and effective role in concluding contracts as an electronic agent. This agent enables the automation of contracts, either wholly or partially, without human intervention. The UAE legislator has shown keen interest in regulating this usage, initially through the Electronic Transactions Law of 2006, then the updated law of 2021, and most recently through the Trade through Modern Technology Law of 2023. This framework considers artificial intelligence an information program that represents the original principal and bears the consequences of the transaction it engages in, despite the absence of legal personality for the electronic agent. The integration of artificial intelligence and modern technologies has profoundly transformed the landscape of commercial law. AI technologies, including natural language processing and machine learning algorithms, are increasingly employed in contract formation, risk assessment, and dispute resolution. These tools enhance efficiency, reduce human error, and streamline transactional processes, benefiting both businesses and consumers. Furthermore, the rise of modern tools such as digital currencies, smart contracts, and blockchain has revolutionized commercial transactions by offering unprecedented levels of transparency, security, and automation. Blockchain ensures immutable and verifiable records, while smart contracts self-execute upon fulfillment of predetermined conditions, reducing reliance on intermediaries and reinforcing transactional integrity. This paper also explores the legal and regulatory responses to these developments. Jurisdictions globally are facing the need to revise existing laws or draft new ones to address the challenges posed by artificial intelligence and emerging commercial technologies. The evolving nature of technology calls for flexible and adaptive legal frameworks to ensure that commercial law remains relevant and effective.The role of artificial intelligence and emerging technologies in UAE commercial transactions law (2023)